Разработка "Цифрового двойника" коронавируса COVID-19 (КК) - Сырямкин, Владимир Иванович; Колтунов, Александр Анатольевич; Клестов, Семен Александрович; Стронин, Олег Владимирович; Берцун, Артемий Николаевич; Сырямкин, Максим Владимирович; Долгая, Дарья Александровна (Инноватика-2021 : сборник материалов XVII Международной школы-конференции студентов, аспирантов и молодых ученых, 22-23 апреля 2021 г., г. Томск, Россия)
The relevance of the topic is due, firstly, to the lack of clarity in the development of this disease and similar diseases in the world, secondly, the uncertainty of its origin (natural-natural or artificial-created by man), and thirdly, the lack of knowledge of its mutation (for people, animals, territories).